AV junction ablation and cardiac resynchronization for patients with permanent atrial fibrillation and narrow QRS: the APAF-CRT mortality trial. (28th August 2021) - Brignole, Michele; Pentimalli, Francesco; Palmisano, Pietro; Landolina, Maurizio; Quartieri, Fabio; Occhetta, Eraldo; Calò, Leonardo; Mascia, Giuseppe; Mont, Lluis; Vernooy, Kevin; van Dijk, Vincent; Allaart, Cor; et al.
Abstract: Aims : In patients with atrial fibrillation (AF) and heart failure (HF), strict and regular rate control with atrioventricular junction ablation and biventricular pacemaker (Ablation + CRT) has been shown to be superior to pharmacological rate control in reducing HF hospitalizations. However, whether it also improves survival is unknown. Methods and results : In this international, open-label, blinded outcome trial, we randomly assigned patients with severely symptomatic permanent AF >6 months, narrow QRS (≤110 ms) and at least one HF hospitalization in the previous year to Ablation + CRT or to pharmacological rate control. We hypothesized that Ablation + CRT is superior in reducing the primary endpoint of all-cause mortality. A total of 133 patients were randomized. The mean age was 73 ± 10 years, and 62 (47%) were females. The trial was stopped for efficacy at interim analysis after a median of 29 months of follow-up per patient. The primary endpoint occurred in 7 patients (11%) in the Ablation + CRT arm and in 20 patients (29%) in the Drug arm [hazard ratio (HR) 0.26, 95% confidence interval (CI) 0.10–0.65; P  = 0.004]. The estimated death rates at 2 years were 5% and 21%, respectively; at 4 years, 14% and 41%. The benefit of Ablation + CRT of all-cause mortality was similar in patients with ejection fraction (EF) ≤35% and in those with >35%. The secondary endpoint combining all-cause mortality or HF hospitalization was significantly lower in the Ablation + CRT arm [18 (29%) vs. 36 (51%); HR 0.40, 95% CI 0.22–0.73; P  = 0.002]. Conclusions : Ablation + CRT was superior to pharmacological therapy in reducing mortality in patients with permanent AF and narrow QRS who were hospitalized for HF, irrespective of their baseline EF. Study registration: ClinicalTrials.gov Identifier: NCT02137187. Graphical Abstract: